The Mozart Sonata and Spatial-Temporal Reasoning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The positive effect of music on spatial-temporal reasoning has been demonstrated in college students using coherence analysis of electroencephalographic (EEG) recordings at the Center for Neurobiology of Learning and Memory and Department of Physics, University of California, Irvine CA.